Amplification of elliptically polarized sub-femtosecond pulses in neon-like X-ray laser modulated by an IR field - I. R. Khairulin; V. A. Antonov; M. Yu. Ryabikin; M. A. Berrill; V. N. Shlyaptsev; J. J. Rocca; Olga Kocharovskaya (Scientific Reports, 2022)
Abstract Amplification of attosecond pulses produced via high harmonic generation is a formidable problem since none of the amplifiers can support the corresponding PHz bandwidth. Producing the well defined polarization state common for a set of harmonics required for formation of the circularly/elliptically polarized attosecond pulses (which are on demand for dynamical imaging and coherent control of the spin flip processes) is another big challenge. In this work we show how both problems can be tackled simultaneously on the basis of the same platform, namely, the plasma-based X-ray amplifier whose resonant transition frequency is modulated by an infrared field.